Stator flux based-MRAS position/speed observer of sensorless switched reluctance motor drives including startup operation - Hady Abdel Maksoud; Mohamed S. Zaky (Ain Shams Engineering Journal)
This paper introduces a new sensorless approach-based model reference adaptive system (MRAS) for switched reluctance motor (SRM). A simplified nonlinear model is derived using phase-inductance-based finite element (FE) analysis. A hybrid sensorless model is integrated to calculate the rotor position over a wide range. MRAS is designed to calculate the speed and rotor position based on a derivative inductance model at all motor speeds unless at starting operation. A simple ramp function with low frequency is utilized to energize the motor phases at a standstill where the electrical quantities are unobservable. The proposed combined sensorless demands neither additional equipment nor sophisticated computation for real execution. To validate the precision and robustness of the suggested observer, simulation and experimental results are presented over a wide range from zero speed to the rated at 1500 rpm. Good accuracy with estimated errors of less than 1 % in most modes of operation is achieved.